INTERACTIVE LEARNING ENVIRONMENT AS PEDAGOGICAL CONDITION OF SUCCESSFUL FOREIGN-LANGUAGE TRAINING OF HEALTH SCIENCES UNIVERSITY STUDENTS - Elena O. Petrova (Открытое образование (Москва), 2016)
This article is devoted to an actual problem of the organization of interactive learning environment for the foreign language speech of medical students and revealing of its role for increase of professional education level. The role and value of applied methodical ware are provided in the article: (introduction of the special course of study "Global Health"; electronic educational and methodical textbook "Training of medical students for the international teleconferences" within the special course of study "Global Health" with the use of interactive methods of training and aimed at the development of speaking skills). The author carried out analysis and assessment of efficiency of influence of the interactive learning environment on the development of IPORK, and received reliable results which testify about positive dynamics of this activity.